Species and Feeding-Guild diversity of Avifauna at Gunung Pinang, Kramatwatu, Serang Regency, Banten - Muhammad, Gema Ikrar; Mardiastuti, Ani; Sunarminto, Tutut (Department of Forest Resources Conservation and Ecotourism - IPB University, 2018)
The objectives of this research was to determine the diversity of species and feeding-guild of avifauna at Gunung Pinang, Banten. This research was conducted in August-December 2017. Data collection was carried out using Point Counts method. Result show that there are 43 species of avifauna from 24 families, 3 species of families Accipitridae among them are migrants. The identified Avifauna was divided into 6 major feed groups i.e insectivor as many as 21 species of birds (49%), frugivor are 7 species (16%), carnivor are 6 species (14%), granivor are 5 species (11%), nectarivor are 2 species (5%) and omnivor that eat more than one type of feed as many as 2 species (5%). Diversity of avifauna at Gunung Pinang considered as high with the index value of shannon diversity is 3.44. The high diversity of avifauna at Gunung Pinang describe the ecological conditions of the ecosystem that can support avifauna as well as a habitat for playing, shelter, rest, foraging, and nesting for avifauna. Keywords: avifauna, diversity, feeding-guild, Gunung Pinang